Chartered Foresters in Madhya Pradesh: a Boon or Bane ? - Kumar, Prasant (Indian Forester, 2005)
Considerable Private Forest areas in Madhya Pradesh are managed scientifically on a sustained basis, under the Lok Vaniki Act, through management plans, prepared by Chartered Foresters. This ensures continuity of management and improvement, as it strikes a balance between aspirations of Bhumiswamis and legal framework including directions of the Supreme Court. The advantages of Chartered Foresters are being realized who want this new concept to be further expanded and become a long. term association. Chartered Foresters are generally retired experienced foresters but there is need to ensure upgrading their professional knowledge periodically, so that he does not become only a middleman, lacking perfect technical skill in preparing management plans which are finally approved by competent authority. However, if the plans are prepared by Bhumiswami's, delays in approval are likely to occur, as the bhumiswamis are unlikely to possess technical competence and adequate regard for sustained exploitation of forests. Chartered Foresters serve as independent third party. Expansion of the role of Chartered Foresters, developing a system of accredition, periodical renewal of knowledge, constituting a regulatory body will go a long way in strengthening this institution as well as removing the maladies which might have crept into this new concept of Private Forests management.